Caregiver-Mediated Intervention Can Improve Physical Functional Recovery of Patients With Chronic Stroke: A Randomized Controlled Trial. (January 2015) - Wang, Tzu-Chi; Tsai, Alan C.; Wang, Jiun-Yi; Lin, Yu-Te; Lin, Ko-Long; Chen, Jiun Jiang; Lin, Bei Yi; Lin, Tai Ching
Background and Purpose. Patients with chronic stroke may benefit from continuing rehabilitation training after hospital discharge. This study examined whether caregiver-mediated, home-based intervention (CHI) could improve physical functioning and social participation in these patients. Methods. A single-blind, randomized, controlled 12-week trial conducted with 51 patients from 3 hospitals in Taiwan who had chronic stroke (>6 months; Brunnstrom recovery stages III-V). Patients and their caregivers in the intervention arm (n = 25) were given weekly personalized CHI trainings designed by a physical therapist. Patients in the control arm (n = 26) received visits from the therapist without intervention. All were evaluated for physical recovery through the Stroke Impact Scale, Berg Balance Scale, 10-Meter Walk Test, 6-Minute Walk Test, and Barthel Index at baseline and endpoint. Caregivers were evaluated with the Caregiver Burden Scale. Results were analyzed through Mann-Whitney U test. Results. CHI significantly improved scores of the Stroke Impact Scale: strength (control vs intervention, respectively: 1.4 vs 15.5; P = .002), mobility (–0.5 vs 13.7; P < .001), composite physical (–0.7 vs 11.2; P < .001), and general recovery domain (0.2 vs 17.4; P < .001). CHI also significantly improved free-walking velocity (–1.4 vs 7.5 cm/s; P = .006), 6-minute walk distance (–10.5 vs 15.8 m; P = .003), Berg Balance Scale score (–0.8 vs 4.5; P = .006), and Barthel Index score (0.6 vs 7.2; P = .008). CHI did not significantly increase caregiver burden at endpoint. Conclusion. CHI can improve physical functional recovery and, possibly, social participation in patients with chronic stroke.